Reformulasi Implementasi Kebijakan Rehabilitasi Narapidana Narkoba dalam Sistem Pemasyarakatan di Lapas Kelas I Palembang - Haris Munandar; Hendri Yansyah; Lufri Yuanda; Wahid Nur Kholif (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The high number of drug convicts in Indonesia, especially in Palembang Class I Prison, shows that the dominant repressive sentencing model has not been effective in reducing drug abuse. This condition has led to overcrowding, which has implications for rehabilitation, health, and potential violations of prisoners' human rights. This study aims to examine the implementation of rehabilitation policies for drug convicts at the Palembang Class I Prison and to offer policy reformulations that are more fair and effective. The method used is normative legal research with a legislative, conceptual, and comparative approach. The findings reveal obstacles in the form of limited infrastructure, a shortage of professionals, social stigma, and regulatory disharmony. Therefore, policy reformulation is necessary through strengthening the legal basis that places rehabilitation as the ultimum remedium, improving rehabilitation facilities and personnel, and community participation in social reintegration. These efforts are expected to create a more humane, effective, and restorative justice-oriented correctional system.